A Reflective Study of Educational Practice in Special Education Colleges - Tariq, Eman; Gul, Fariha; Asif, Awaiz (Annals of Human and Social Sciences, 2023)
This study investigated the educational practices of 100 students enrolled in special education colleges. The objective of this study was to identify the practices and strategies that have been successful in improving the educational outcomes of special education students. The results of the study revealed that students who have had successful educational experiences in special education colleges often participated in a variety of practices and strategies such as regular communication with instructors, active participation in class activities, and a focus on individualized learning plans. Additionally, the study revealed that providing tailored support and resources to students was an important factor in improving educational outcomes. The study also found that successful educational outcomes were associated with regular collaboration between teachers and students.